Interactive Control System, Intended Strategy, Implemented Strategy dan Emergent Strategy - Tubagus Ismail; Darjat Sudrajat (Bina Nusantara University, 2012)
The purpose of this study was to examine the relationship between management control system (MCS) and strategy formation processes, namely: intended strategy, emergent strategy and impelemented strategy. The focus of MCS in this study was interactive control system. The study was based on Structural Equation Modeling (SEM) as its multivariate analyses instrument. The samples were upper middle managers of manufacturing company in Banten Province, DKI Jakarta Province and West Java Province. AMOS Software 16 program is used as an additional instrument to resolve the problem in SEM modeling. The study found that interactive control system brought a positive and significant influence on Intended strategy; interactive control system brought a positive and significant influence on implemented strategy; interactive control system brought a positive and significant influence on emergent strategy. The limitation of this study is that our empirical model only used one way relationship between the process of strategy formation and interactive control system.